A histological study on the effect of pressure therapy on the activities of myofibroblasts and keratinocytes in hypertrophic scar tissues after burn. Issue 5 (August 2015) - Li-Tsang, Cecilia W.P.; Feng, Beibei; Huang, Lin; Liu, Xusheng; Shu, Bin; Chan, Yvonne T.Y.; Cheung, Kwok-Kuen
Highlights Pressure therapy elicited an early yet positive response of hypertrophic scars (HS). The intervention significantly improved the thickness and redness of HS. Proliferation of basal keratinocytes in HS was inhibited after the intervention. Reduction in myofibroblasts was correlated with increase in apoptosis in dermal layer.